(untitled) (Estudios Sociales, 2024)
This article analyzes the state presence through social policies and the experiences and perceptions of the «beneficiaries» about that presence in the city of Chascomús, province of Buenos Aires, in 2022. A case study was carried out, through Secondary sources and interviews identified the programs of the different levels of the State that are implemented at the local level. Given the difficulties in recognizing a family group that has access to all the programs that, according to their situations, the State makes possible, we worked with a «fictitious» family. At the same time, ten interviews were conducted with «beneficiaries» of the programs. The analysis revealed the fragmentation of social policies and that even families that access a multiplicity of programs are not guaranteed the Total Basic Basket. It is argued that the fragmented presence of the State does not strengthen the social bond and constitute assisted subjects.